A Cyclic Silylone ("Siladicarbene") with an Electron‐Rich Silicon(0) Atom1. Issue 28 (31st May 2013) - Xiong, Yun; Yao, Shenglai; Inoue, Shigeyoshi; Epping, Jan Dirk; Driess, Matthias
<x xml:space="preserve">Abstract</x> King of donor: The chelating bis(carbene) 1 enabled the synthesis of the new silyliumylidene salt 2. This salt can be dechlorinated with sodium naphthalenide to give the first cyclic siladicarbene 3, which bears a single Si0 atom with strikingly high basicity. The small C‐Si‐C angle of 89.1° and the average CSi distance of 1.869 Å are consistent with results from theoretical calculations, which revealed that 3 is best described as a silylone.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>